Penyuluhan Kesehatan Pola Hidup Sehat Pada Lansia dan Bakti Sosial di Panti Sosial Wardha Tresna Kelurahan Tendeadongi Kecamatan Pamona Utara - Niluh Puspita Dewi niluh; Indah Kurnia Utami; Wayan Wirawan (Duta Abdimas, 2023)
Counseling is a method that is carried out by someone to obtain health information or maximum health status. Aging is a period of change experienced by individuals both physically and psychologically due to decreased body function. This will affect various aspects of life in old age. So that it requires maintenance that is different from the age of children, adolescents, and adults who need support from those around them. Successful psychological aging is reflected in the ability of elderly individuals to adapt to physical, social and emotional life and achieve happiness, peace and life satisfaction. A person's lifestyle plays an important role in determining the aging process. This is proven with reports that 64% of the causes of death are caused by an unhealthy lifestyle healthy. Setting a lifestyle that includes patterns of sleeping, eating, working, resting, and recreation is very important determine a person's age This counseling aims to enable the elderly to be able to maintain independence and quality of life in order to achieve welfare for the elderly at the Wardha Tresna Social Institution. Counseling is given by interactive lecture method through posters and distribution of leaflets as well as social services. The effectiveness of counseling was tested by administering a questionnaire on partner satisfaction with the activities carried out. The results of observing the activities show that Partners are satisfied with the counseling activities carried out.